Mobile Application of Searching and Mapping Temporary Waste Disposal Site in Fakfak Regency - Riyadh Arridha; Nur Sakinah; Titing Magfirah (Jurnal Mantik, 2022)
Nowadays, humans live in technological era called modern. Smartphone is a kind of technology that has function to access information including services or public facilities information. One of the public facilities that public needs to know about is the location of a temporary waste disposal site (TPS). The lack of information about the location of TPS triggers irresponsible behavior including littering, the emergence of illegal dumpsters, and the emergence of garbage piles in waterways which can lead to flood. Geographic Information System (GIS) is one of the technologies that can be used to help the public knows the location of TPS as well as the route to the desired TPS. Besides, it provides information about the route of the desired TPS location. This study aims to build a Mobile Application for Mapping and Searching for Temporary Waste Disposal Site (TPS) with a Case Study in Fakfak Regency, West Papua Province. This system is built through combination of web application as a backend and mobile application as a frontend by utilizing features from Google Maps. This research generally uses the Waterfall method, where the implementation is systematic with several stages, namely; system requirements analysis, system design, system making, system testing and repair, and maintenance and repair. Based on the test results using Black Box method, it shows the application is functionally running well. Meanwhile, the testing result by users using a questionnaire reveals that there are >80% of users gave a good and very good assessment of the built application.